Trafficking in Persons and Human Development: Towards A More Integrated Policy Response - Danailova-Trainor, Gergana
Poverty is often regarded as the "root cause" of trafficking, but the linkages between poverty, lack of development and trafficking are complex. For example, there is some evidence to suggest that victims of cross-border trafficking are more likely to originate from middle-income rather than lower-income countries. Trafficking and development have tended to be treated as very separate policy areas and the assessment of the development impact of counter-trafficking programmes is still at an early stage. This paper outlines a possible framework for a more evidence-based approach to understanding the linkages between trafficking, trafficking policy and human development. The paper argues that the human development gains from greater mobility could be significantly enhanced if there was greater coherence between policies to combat trafficking and policies to promote development.Human Trafficking, Development, Evaluation, Poverty Reduction Strategies, Policy Coherence.